Rituximab-associated adverse events in nephrotic syndrome: A systematic review and meta-analysis - Zixian Yu; Meijin Huang; Yunlong Qin; Xiayin Li; Yueru Zhao; Yuwei Wang; Yumeng Zhang; Anjing Wang; Mei Han; Jin Zhao; Shiren Sun (Heliyon)
Objective: Rituximab (RTX) has been recommended to treat nephrotic syndrome (NS), but its safety has not been quantitatively analyzed. Methods: PubMed, Embase, and the Cochrane Register of Controlled Trials databases were searched from inception to December 31, 2023, for randomized control trials (RCTs) and retrospective studies reporting the adverse events (AEs) related to RTX for treating NS. Data were expressed as odds ratios (OR) and risk difference (RD) with 95 % confidence interval (CI). Heterogeneity was identified using the Cochrane Q test and quantified by the I2 statistic. Results: Ten RCTs and five retrospective studies with 1231 patients were enrolled. RTX significantly reduced the risk of total AEs (OR = 0.32, 95 % CI [0.13, 0.78]) compared to the non-RTX group in retrospective studies but was not in RCTs. The pooled rate of infusion reactions was 32 % (95 % CI = [19 %, 45 %]) in RCTs and 8 % (95 % CI = [3 %, 13 %]) in retrospective studies. Subgroup analyses demonstrated a lower risk of hematological events in adult NS patients (OR = 0.21, 95 % CI [0.09, 0.51]) and the 1000 mg RTX intervention (OR = 0.21, 95 % CI [0.09, 0.51]). There is no significant difference in serious AEs, infection, gastrointestinal, renal, cardiovascular, and cancer events between the two groups. Conclusion: RTX reveals great potential in terms of safety compared to non-RTX treatments due to the relatively few AEs in our results. However, the interaction of other drugs needs to be monitored. The safety of RTX in NS patients needs to be further confirmed in high-quality clinical trials.